Banks fearing the drought? Liquidity hoarding as a response to idiosyncratic interbank funding dry-ups - Helge C. N. Littke; Matias Ossandon Busch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
Since the global financial crisis, economic literature has highlighted banks' inclination to bolster up their liquid asset positions once the aggregate interbank funding market experiences a dry-up. To this regard, we show that liquidity hoarding and its detrimental effects on credit can also be triggered by idiosyncratic, i.e. bankspecific, interbank funding shocks with implications for monetary policy. Combining a unique data set of the Brazilian banking sector with a novel identification strategy enables us to overcome previous limitations for studying this phenomenon as a bankspecific event. This strategy further helps us to analyse how disruptions in the bank headquarters' interbank market can lead to liquidity and lending adjustments at the regional bank branch level. From the perspective of the policy maker, understanding this market-to-market spillover effect is important as local bank branch markets are characterised by market concentration and relationship lending.
urn:nbn:de:gbv:3:2-93042
Keywords: G01; G11; G21; 330; financial crisis; interbank market; liquidity risk